Evaluation of Biomedical Infor matics Innovations and Their Impact on Public Health - Sarkar, I. N. (Methods of Information in Medicine, 2012)
This issue of Methods of Information in Medicine contains four feature articles that are focused on the theme of evaluation. Evaluation approaches are increasingly essential in the assessment of determining the potential impact of contemporary informatics innovations. The featured articles offer practical perspectives to determining the impact of advancements. Internationally, there are significant advances being made across biomedical informatics and its related sub-disciplines. As with any scientific discipline, it is important for practitioners to be able to relate the potential importance of findings. To this end, it is especially important for biomedical informaticians to convey, in a quantifiable and comparable form, the significance of the informatics findings – not only to peers but also to those across the biomedical research spectrum. As such, the feature articles in this issue describe the evaluation of core infrastructure and fundamental informatics innovations as well as evaluation of informatics-based resources that are a core aspect of public health initiatives.
Keywords: Biomedical informatics; health informatics; public health informatics; evaluation